Al-Kafā’ah (Compatibility) Between Spouses Regarding Righteousness as Discussed in the Tafsīr of Al-Ourṭubi: Implications for Marital Life - Hassan, Muhammad Kannike (KWASU Journal of Religious Studies, 2018)
Choice of marital partner is determined by a number of catalysts one of which is al-kafā’ah (equality of status) between spouses. Some marriages cause a sort of antipathy which leads to discord and separation between the couples as a result of incompatibility emanating from disequilibrium of moral, religious or socio-economic status of the spouses. Jurists hold divergent opinions on qualities which should be considered as genuine criteria for al-kafā’ah as various contemporary societies differ in what they determine as criteria for compatibility between spouses. In this wise, the Qur’ānic paradigm relating to the issue of al-kafā’ah was exposed by al-Qurtubi in his Tafsīr. This paper, therefore, examines al-Qurtubi’s exegetical discourse on al-kafā’ah between spouses with the intent of identifying genuine criteria for the compatibility and their implications for marital life. Exegetical and analytical methods were adopted for the study. It identifies religion and piety as the basic criteria for the compatibility of status which help to maintain decency and wellbeing of individuals in marital life, while socioeconomic status may be waived, but with the consent of wife in order to curb psychoemotional disturbance resulting from mis-merge of socio-economic statuses. It also pointed out that repentance of unchaste spouse is considerable, and the chaste has the right to either retain the existing marriage with the persistent unchaste or dissolve it for the interest wellbeing of marital life. The study concludes that al-Qurtubi was able to deduce the criteria for the compatibility of status between spouses, from the Qur’ān.